Plant biochemistry and molecular biology - Hans-Water Heldt (Oxford Univ. Press, 1999)
The book provides a thorough graounding in the subject to an advanced level, covering photosynthesis, primary and secondary metabolism, the function of photohirmones, and molecular engineering. It also describes the many practical commercial applications of plant biochemistry, molecular biology, and technology, for example the use of genetic engineering to improve crop plants and to provide sustainable raw materials for the chemical and pharmaceutical industries.